Numerical investigation of the influence of tip clearance and rotor-stator interaction on centrifugal pump performance and cavitation - Cong Liu (Tehnički Glasnik, 2017)
The influence of tip clearance on pump performance and the impact of the rotor-stator interaction on cavitation are investigated by numerical means, respectively. Firstly, the SST model is employed in numerical anaylsis, and the numerical investigation of the pump performance based on a different turbulence model is compared with the experimental data. Secondly, the pump performance at different tip clearances is investigated, and the numerical results indicate that the smaller tip clearance the better performance of keeping the head stable at a low mass flow rate. Thirdly, as the NPSH-Head curves are computed at different tip clearances, the conclusion can be drawn that the smaller the tip clearance, the stronger the capability of preventing cavitation. Lastly, the effect of the rotor-stator interaction on cavitation is performed at a design case, when the φ = 9°, the volume fraction of cavitation is maximum, however, when the φ = 120°, the volume fraction of cavitation is minimum. Besides, the blade loading is studied at a corresponding φ value. When the φ = 44°， the blade loading is minimum, however, when the φ = 120°, the blade loading is maximum. The cavity all appears from the leading edge to the 20% chord length for a different φ value, which indicates that the cavitation zone grows along the normal direction of the suction surface.